Genome-wide association study with DNA pooling identifies variants at CNTNAP2 associated with pseudoexfoliation syndrome - Krumbiegel, Mandy; Pasutto, Francesca; Schlötzer-Schrehardt, Ursula; Uebe, Steffen; Zenkel, Matthias; Mardin, Christian; Weisschuh, Nicole; Paoli, Daniela; Gramer, Eugen; Becker, Christian; Ekici, Arif Bülent; Weber, Bernhard H. F.; et al. (European journal of human genetics, 2011)
Genetic and nongenetic factors contribute to development of pseudoexfoliation (PEX) syndrome, a complex, age-related, generalized matrix process frequently associated with glaucoma. To identify specific genetic variants underlying its etiology, we performed a genome-wide association study (GWAS) using a DNA-pooling approach. Therefore, equimolar amounts of DNA samples of 80 subjects with PEX syndrome, 80 with PEX glaucoma (PEXG) and 80 controls were combined into separate pools and hybridized to 500K SNP arrays (Affymetrix). Array probe intensity data were analyzed and visualized with expressly developed software tools GPFrontend and GPGraphics in combination with GenePool software. For replication, independent German cohorts of 610 unrelated patients with PEX/PEXG and 364 controls as well as Italian cohorts of 249 patients and 190 controls were used. Of 19, 17 SNPs showing significant allele frequency difference in DNA pools were confirmed by individual genotyping. Further single genotyping at CNTNAP2 locus revealed association between PEX/PEXG for two SNPs, which was confirmed in an independent German but not the Italian cohort. Both SNPs remained significant in the combined German cohorts even after Bonferroni correction (rs2107856: P(c)=0.0108, rs2141388: P(c)=0.0072). CNTNAP2 was found to be ubiquitously expressed in all human ocular tissues, particularly in retina, and localized to cell membranes of epithelial, endothelial, smooth muscle, glial and neuronal cells. Confirming efficiency of GWAS with DNA-pooling approach by detection of the known LOXL1 locus, our study data show evidence for association of CNTNAP2 with PEX syndrome and PEXG in German patients.
EVALuna2:9084